Random-Rate Processes in Navigation in Bacteria, Archaea, and Desert Ants - Ken Cheng (Psychological Topics)
Movement in life is usually carried out by effectors, body parts that carry out action such as flagella, archaella, cilia, whole bodies that sinuate, or limbs, moving regularly and periodically in an oscillator system. For navigation and orientation, the oscillations that generate movement are sometimes interrupted by stops, turns, or both. I review evidence in bacteria, archaea, and one animal, the Australian desert ant Melophorus bagoti, that such interruptions to forward movement take place as random-rate or Poisson processes. At every moment in time, there is a constant probability of the event taking place. On looking for explanations for such random-rate events, some evidence suggests that the bacterium Escherichia coli relies on stochastic or random fluctuations to generate turns. I conjecture that relying on noise makes a cheap mechanism in the sense that no dedicated mechanism for generating occasional interruptions is required. Random processes mostly come ‘for free’. The data are too sparse and uncertain for archaea and ants to attempt any explanation. It is not necessary to rely on noise or stochastic processes to produce what look like random fluctuations; various nonlinear mechanisms might do that. My call to action to those studying behaviour is to examine much more the interval or duration of time between events.